First record of the genus Gomesius (Hemiptera: Heteroptera: Reduviidae: Emesinae) from India, with description of a new species - Ghate, H.v.; Mathew, Mirjoy (Zootaxa, 2018)
Gomesius indicus sp. nov. (Hemiptera: Heteroptera: Reduviidae: Emesinae: Leistarchini), collected in Goa State, India, is described. This is the first record of the genus Gomesius Distant, 1903, from India.